Abrasion of Pro Seal® and Opal® Seal™ by professional tooth cleaning protocols: results from an in vitro study and a randomized controlled trial. (25th November 2019) - Deurer, Nadine; Erber, Ralf; Orhan, Gül; Zingler, Sebastian; Lux, Christopher J; Şen, Sinan
Summary: Background: The integrity of orthodontic surface sealants after professional tooth cleaning (PTC) has previously only been evaluated in vitro . Recently, we have shown that optical coherence tomography (OCT) can successfully be used for the longitudinal assessments of sealant thickness in vitro and in vivo . Objectives: Thus, the aim of the present study was to assess the sealant thickness after PTC in vitro and in vivo by OCT. Trial design: Single-centre four-arm parallel-group randomized controlled trial. Methods: Ninety-six extracted human teeth were randomly assigned to the surface sealants Pro Seal® (PS) and Opal® Seal™ (OS) and to PTC protocols: (1) polishing with brush and prophy paste (Cleanic®) or (2) erythritol air-polishing. Sealant thickness was assessed by OCT immediately after application (baseline), after thermocycling and after polishing for totals of 5, 10, 15, 30, 60, 90, and 120 seconds. Additionally, a clinical trial was conducted. Therefore, using a split-mouth design, quadrants of 20 patients and PTC protocols were randomized by an external randomization centre using computer generated tables to assign the surface sealants and PTC protocols. Sealant thicknesses were analysed at baseline, before and after PTC. Due to the optical properties of sealants, a complete blinding was not feasible. Results: In vitro both sealants revealed significant layer thickness losses after both PTC protocols. PS lost 0.77 µm/s [95% CI (confidence interval): 0.67, 0.87] from air-polishing and 0.43 µm/s (95% CI: 0.37, 0.49) from polishing with brush while OS lost 0.44 µm/s (95% CI: 0.32, 0.55) from air-polishing and 0.79 µm/s (95% CI: 0.68, 0.89) from polishing with brush of layer thickness. Sealant thickness loss of was significantly higher after erythritol air-polishing for PS and after polishing with brush for OS. The results of a concurrent randomized controlled trial (RCT) were comparable to those achieved in the in vitro part of this study. Limitations: Long-term surface sealant abrasion should be validated by additional RCTs. Conclusions: For PTC on surface sealant treated teeth, low abrasive protocols should be used. Air-polishing should be avoided on PS protected teeth and polishing with brush on OS treated teeth. Trial registration: ClinicalTrials.gov NCT03753256.